Early Marriage and Reproductive Health: A Scientific Study on Risks and Consequences - Nirwan, Multy Syaddam (Yayasan Sinergi Kawula Muda, 2023)
Early marriage remains a critical global issue with significant implications for reproductive health, education, and economic stability. This study examines the adverse effects of early marriage, emphasizing its impact on maternal health, educational attainment, and socio-economic opportunities. Using a systematic literature review, data were collected from academic databases such as PubMed, Scopus, and Google Scholar to analyze trends and factors contributing to early marriage. The results indicate that women who marry before the age of 18 face higher risks of pregnancy complications, maternal mortality, and limited access to reproductive healthcare. Additionally, early marriage significantly reduces educational opportunities, leading to economic dependence and perpetuating poverty cycles. Cultural and religious factors, along with socio-economic pressures, play crucial roles in sustaining this practice. Policy recommendations include improving girls' access to education, implementing comprehensive sexuality education, enforcing legal frameworks against child marriage, and engaging communities in intervention programs. Future research should explore digital strategies to increase awareness and prevention efforts. Addressing early marriage requires a multidisciplinary approach integrating health, education, and socio-economic policies to promote gender equality and reproductive health rights.